A Framework of Critical Success Factors for Change Management in Digital Transformation Initiatives within the Public Sector - Gauchon, Justine (My University, 2023)
This master's thesis presents a comprehensive framework for identifying and managing Critical Success Factors (CSFs) in Change Management within Digital Transformation (DT) initiatives. The significance of DT, particularly in the public sector, is emphasized due to its potential to revolutionize operations, enhance service delivery, and improve citizen engagement. Yet, 70% of the DT initiatives fail, mainly due to resistance coming from people. Change management is explored as a crucial process that facilitates the successful implementation of DT, ensuring that organizational members embrace and adapt to the changes effectively. Drawing from an extensive literature review, five key CSFs are identified: Organizational Effectiveness, Change Commitment, Project Management, IT/Technology, and External Environment. These factors are considered essential for enabling a smooth and successful transition in DT initiatives. To validate the framework, three case studies and seven interviews are conducted, providing empirical evidence and insights into the practical application of the CSFs. Overall, this thesis offers a valuable contribution to the field of Change Management in DT, providing a structured approach for organizations, especially in the public sector, to navigate the complexities and challenges associated with these transformative projects.
Keywords: Change Management, Digital Transformation, Critical success factors, Public Sector